Directed transport of liquid droplets on vibrating substrates with asymmetric corrugations and patterned wettability: a dissipative particle dynamics study. Issue 1 (2nd January 2020) - Geng, Xinran; Yu, Xiaopeng; Bao, Luyao; Priezjev, Nikolai V.; Lu, Yang
ABSTRACT: The development of digital (droplet-based) microfluidic (DMF) devices has received significant attention due to their importance for chemical and biomedical analyses. The precise control and manipulation of liquid droplets on a solid substrate is a major requirement for DMF devices. In this study, we propose a novel strategy to generate continuous droplet motion by combining asymmetric corrugations and patterned wettability on a vibrating substrate. The time periodic oscillations of the substrate with asymmetric triangle corrugations provide the input energy to transport a droplet along patterned stripes. Using dissipative particle dynamic (DPD) simulations, we demonstrate that hydrophobic stripes on a superhydrophobic substrate create a wettability step, which effectively constrains the droplet motion along the stripe. Due to the special design of asymmetric triangle corrugations and orientation of hydrophobic stripes, the proposed strategy enables the transport of multiple droplets with different initial locations towards a single spot and coalescence into a large droplet. We further identify a power-law dependence between the droplet velocity and the period of substrate vibration and show that this function is independent of the droplet size. The proposed droplet transportation strategy can be potentially useful for the efficient manipulation of liquid droplets in DMF devices.